2013
DOI: 10.1063/1.4820422
|View full text |Cite
|
Sign up to set email alerts
|

Field emission from laterally aligned carbon nanotube flower arrays for low turn-on field emission

Abstract: Laterally aligned carbon nanotube (CNT) arrays “blossomed” homogeneously in honeycomb holes of a metal grid substrate were explored as rational architecture for field emission. A low turn-on field (TOF) of 1.09 V/μm for 10 μA/cm2 emission was achieved, which approaches or exceeds the lowest reported TOF values for field emitter arrays. We interpret that these lateral CNT arrays act as source of CNT “loop” arrays enabling a structure suited toward low TOF field emission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In spite of this lateral growth a good FEF is observed here. The reason may be the fact that here emission from CNTs have been much less hampered by screening effects from neighboring tubes [42][43][44]. In their extensive studies on the screening effect on the field emission behavior of CNTs, Nilsson et al [44] has shown that morphology of the individual CNTs as well as the distance between two CNTs are decisive for getting high field-emission current density.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In spite of this lateral growth a good FEF is observed here. The reason may be the fact that here emission from CNTs have been much less hampered by screening effects from neighboring tubes [42][43][44]. In their extensive studies on the screening effect on the field emission behavior of CNTs, Nilsson et al [44] has shown that morphology of the individual CNTs as well as the distance between two CNTs are decisive for getting high field-emission current density.…”
Section: Discussionmentioning
confidence: 98%
“…Suh et al [43] showed that FEF increases with aspect ratio initially and attains a maxima when inter tube distance is comparable to tube height and then it decreases again when inter tube distances become less than the tube height. Kimura et al [42] showed that this screening effect problem is lesser for lateral growth and hence it enhances the field emission current density of CNTs. Thus, the lateral forest like growth that is observed here may actually help in enhancing the FEF here instead of reducing it.…”
Section: Discussionmentioning
confidence: 99%
“…Flower like structures are self-assembled 1D or 2D nanostructures having large proportions of numerous thin open edges, which make them a favorable material for eld emission applications. [25][26][27][28][29] Aligned CNT ower arrays have been reported to act as a suitable low turn on eld emission device due to better lateral emission from CNTs than from their top surface. 25,29 Graphene owers exhibits enhanced eld emission properties due to the electric eld enhancement on the edges of the nano-slices and the sp 3 -like defects on the surface of the nanocrystalline graphitic lm.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, chemical vapor deposition (CVD) technique has been widely introduced to produce vertically aligned, periodic, similar alignment, orientation, and lengths of nanostructure arrays having high aspect ratio. [9][10][11] Their symmetry is related to the orientation of the hexagonal lattice with respect to the axis of the tube. Although many researchers have worked on different catalysts to synthesize pillar-shaped vertically aligned CNTs but still there is a lot of permutation and combination required to prepare a low cost catalyst which can enhance the growth rate, purity as well as crystalline structure of the CNTs suitable for different applications.…”
Section: Introductionmentioning
confidence: 99%